Garnet type microwave dielectric ceramic with low dielectric constant and preparation method thereof
By introducing Ni2+ and V5+ ions into garnet-type microwave dielectric ceramics, Ca3Ni2SiV2O12 ceramics were prepared, solving the problem of high cost caused by high-temperature sintering and achieving excellent comprehensive performance of low dielectric constant and high Q value, making it suitable for high-frequency communication systems.
Patent Information
- Application Number
- CN202511368625.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-24
- Publication Date
- 2025-10-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing microwave dielectric ceramic materials are sintered at high temperatures, resulting in high manufacturing costs and difficulty in simultaneously possessing low dielectric constant, low temperature coefficient of resonant frequency, and high Q value, thus limiting their application in high-frequency communications.
A dense ceramic material was prepared by using a low dielectric constant garnet-type microwave dielectric ceramic with the chemical formula Ca3Ni2SiV2O12, which lowered the sintering temperature and optimized the microstructure by introducing Ni2+ and V5+ ions.
It achieves excellent dielectric properties with low dielectric constant, low sintering temperature and high Q value, making it suitable for high-frequency communication systems and improving the system's performance stability and reliability.
Smart Images

Figure CN120864880A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dielectric ceramics technology, and particularly relates to a low dielectric constant garnet-type microwave dielectric ceramic and its preparation method. Background Technology
[0002] Microwave dielectric ceramics refer to ceramics used as dielectric materials in microwave frequency bands (mainly UHF and SHF bands, 300MHz to 300GHz, corresponding to wavelengths from 1 m to 1 mm) circuits, performing one or more functions. In microwave frequency band circuits of electronic components, they serve as dielectric materials, acting as dielectric isolation, dielectric waveguides, and dielectric resonances. They are widely used in microwave resonators, filters, oscillators, capacitors, and microwave substrates, and are key materials for modern microwave communications such as mobile communications, satellite communications, GPS, Bluetooth technology, and wireless LANs. Microwave communication technology has advantages such as strong anti-interference capabilities, large carrier capacity, and high data transmission capacity, and has extensive and in-depth applications in military, civilian communications, satellite communications, aerospace, and other fields.
[0003] With the advent of 5G and the future 6G era, wireless communication technology is gradually developing towards millimeter-wave transmission, which places higher demands on communication systems, including higher frequency, integration, high reliability, and low latency. Therefore, signal transmission delay and bandwidth have become a key research focus. Based on the positive correlation between signal delay time and dielectric constant... , where t d Indicates the signal delay time, l c Let c be the transmission distance, c be the speed of light, and ε be the transmission distance. r [Dielectric constant], a lower dielectric constant helps reduce the delay time of electromagnetic waves propagating in a medium. Furthermore, a low dielectric constant means a lower degree of polarization of the material under an electric field, thus effectively reducing the delay and energy loss of microwave signals during transmission, improving signal transmission quality and efficiency. In applications such as high-frequency communication, satellite communication, and radar, the use of microwave dielectric ceramic materials with low dielectric constants can significantly enhance the performance stability and reliability of the system. Simultaneously, to achieve low loss and good thermal stability in microwave devices, the material also needs to possess a high Q value (quality factor Q×f) and a near-zero temperature coefficient of resonant frequency (τ). f ).
[0004] Currently, several inorganic compounds with low dielectric constants have been reported in the literature, most of which are aluminate and silicate systems. The crystal structures of these candidate materials are mainly composed of tetrahedral structural units (such as AlO4 and SiO4). From a crystallographic perspective, the small gaps between tetrahedral structures limit the space provided for cation vibrations, resulting in weaker polarization of ions or electrons, thus exhibiting a low dielectric constant. Garnet is a diverse class of silicate minerals with the general chemical formula A3B2C3O. 12 In this general formula, A, B, and C represent the coordination positions occupied by different cations in the crystal structure. The A-site is typically occupied by a divalent cation, located in an octahedral coordination environment; the B-site is mainly occupied by a trivalent cation, located in a hexavalent octahedral structure; and the C-site is typically occupied by a smaller tetravalent cation (most commonly Si). 4+ The cations at the A, B, and C positions are filled with tetrahedral coordination units. These structural units (dodecahedral, octahedral, and tetrahedral) are interconnected through shared oxygen atoms, forming a stable three-dimensional crystal framework. Garnet possesses cubic crystal symmetry (space group Ia3d), and the A, B, and C positions have broad substitution capabilities, resulting in various chemical variants (such as pyrope, almandine, and grossular), thus endowing it with diverse physical properties and broad application prospects. However, aluminates and silicates typically require high-temperature sintering (up to 1500℃) to obtain dense ceramic bodies, and silicate garnet ceramics also require high sintering temperatures. Therefore, achieving phase synthesis, ceramic densification, and reducing manufacturing costs pose significant challenges, which to some extent limits its feasibility in practical applications.
[0005] Therefore, a low dielectric constant ε was developed. r It possesses both a high Q value and a near-zero temperature coefficient of resonant frequency (τ). f Microwave dielectric ceramic materials with significantly reduced sintering temperatures are a major research topic in the field of microwave dielectric ceramics technology. Summary of the Invention
[0006] In order to develop a low dielectric constant ε r It possesses both a high Q value (quality factor Q×f) and a near-zero temperature coefficient of resonant frequency (τ). f This invention proposes a low dielectric constant garnet-type microwave dielectric ceramic and its preparation method, which has a low sintering temperature and is a microwave dielectric ceramic material.
[0007] To achieve the above objectives, the present invention provides the following technical solution: A low dielectric constant garnet-type microwave dielectric ceramic with the chemical formula Ca3Ni2SiV2O 12 .
[0008] The preparation method of this low dielectric constant garnet-type microwave dielectric ceramic includes the following steps: S1, the original powders of CaCO3, NiO, V2O5 and SiO2 are arranged according to Ca3Ni2SiV2O 12 The components are weighed and mixed. S2, Wet ball mill the original powders weighed in step S1 to obtain a mixed slurry; S3, the mixed slurry is dried and pre-calcined to obtain mixture A; S4, add binder to mixture A and granulate, then shape to obtain green body; S5, the green blank is sintered to obtain Ca3Ni2SiV2O 12 Microwave dielectric ceramics.
[0009] Furthermore, the purity of the original powders of CaCO3, NiO, V2O5 and SiO2 in step S1 is not less than 99.99%.
[0010] Furthermore, in step S2, the wet ball milling time is 6 hours, and the ball milling medium is deionized water.
[0011] Furthermore, the pre-firing in step S3 is carried out in an atmospheric atmosphere, with a heating rate of 5°C / min, a pre-firing temperature of 900°C, and a pre-firing time of 4 to 8 hours.
[0012] Furthermore, in step S4, the mass of the binder accounts for 1.5 to 3% of the mass of mixture A.
[0013] Furthermore, in step S4, the adhesive is a 5% polyvinyl alcohol solution.
[0014] Furthermore, the sintering in step S5 is carried out in an atmospheric atmosphere, with a heating rate of 5℃ / min, a sintering temperature of 1080~1160℃, and a sintering time of 4~8 hours.
[0015] The beneficial effects of this invention are: by simultaneously introducing Ni into the silicon-based garnet structure 2+ and V 5+ The two ions can effectively alleviate the high-temperature sintering conditions required for densification of silicon-based garnets, reduce the sintering temperature and optimize the microstructure, thereby obtaining ceramics with a dense microstructure. This allows the ceramics to achieve excellent comprehensive dielectric properties, including low dielectric constant, low sintering temperature, high quality factor and near-zero resonant frequency temperature coefficient. The microwave dielectric ceramic of this invention has a dense and stable crystal structure and excellent performance, making it a promising candidate formulation for high-performance microwave dielectric ceramic materials. Attached Figure Description
[0016] Figure 1 The Ca3Ni2SiV2O sintered at 1080℃ in Example 1 12 Microscopic images of ceramics.
[0017] Figure 2 The Ca3Ni2SiV2O sintered at 1140℃ in Example 2 12 Microscopic images of ceramics.
[0018] Figure 3 The Ca3Ni2SiV2O sintered at 1160℃ in Example 3 12 Microscopic images of ceramics.
[0019] Figure 4 For Comparative Example 1, Ca3Ni2SiV2O was sintered at 1060℃. 12 Microscopic images of ceramics.
[0020] Figure 5 For Comparative Example 2, Ca3Ni2SiV2O was sintered at 1200℃. 12 Photos of actual ceramic items.
[0021] Figure 6 For Ca3Ni2SiV2O at different sintering temperatures (1080℃, 1100℃, 1120℃, 1140℃, 1160℃) 12 XRD pattern of ceramics. Detailed Implementation
[0022] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings.
[0023] This invention proposes a low-dielectric-constant garnet-type microwave dielectric ceramic and its preparation method. The general structural formula of garnet is A3B2C3O. 12 In its structure, the A, B, and C sites of the ion coordinate with oxygen atoms to form dodecahedral, octahedral, and tetrahedral structures, respectively. Element A is typically a +1 alkali metal or a +2 alkaline earth metal ion, B is typically a +3 ion, and C is a +3, +4, or +5 transition metal ion. When the C site is occupied by Al… 3+ Ga 3+ Si 4+ When occupied, the sintering temperature is generally high (above 1400℃). When all C sites are occupied by V... 5+ Due to their inherent characteristics, the sintering temperature is generally low. Therefore, this invention introduces Ni into the silicon-based garnet structure simultaneously. 2+ and V 5+Two ions effectively alleviate the high-temperature sintering conditions required for densification of silicon-based garnets, lowering the sintering temperature and optimizing the microstructure to obtain ceramics with a dense microstructure. Simultaneously, they achieve low dielectric constant and low sintering temperature while maintaining a high quality factor and a near-zero temperature coefficient of resonant frequency. Specifically, the chemical formula of the low-dielectric-constant garnet-type microwave dielectric ceramic of this invention is Ca3Ni2SiV2O. 12 .
[0024] This invention, Ca3Ni2SiV2O 12 The low dielectric constant garnet-type microwave dielectric ceramic was prepared by a solid-state reaction method. The chemical reactions involved in the preparation process are as follows: 3CaCO3+ 2NiO+V2O5+ SiO2→ Ca3Ni2SiV2O 12 + 3CO2↑
[0025] The Ca3Ni2SiV2O of the present invention 12 The preparation method of low dielectric constant garnet-type microwave dielectric ceramics is as follows: Step 1: Mix the original powders of CaCO3, NiO, V2O5, and SiO2 according to the formula Ca3Ni2SiV2O 12 The components are weighed and mixed; preferably, each of the above raw materials has a purity of not less than 99.99%. Step 2: Add the weighed raw powders to a ball mill for wet ball milling. The ball milling medium is deionized water, the ball milling time is 6 hours, and the ball milling speed is 300 r / min. Step 3: Dry the slurry obtained from ball milling at a temperature of 120°C; pre-calcine the dried powder in a muffle furnace in an atmospheric atmosphere at a heating rate of 5°C / min, at a pre-calcine temperature of 900°C, for 4-8 hours, to obtain mixture A after pre-calcine. Step 4: Add a binder to mixture A and granulate to obtain powder. Then, press the powder into a green body. The binder is a 5% polyvinyl alcohol solution (PVA) with a mass concentration of 1.5-3% of the mass of mixture A, preferably 2.5%. The molding process is dry pressing. The molding equipment is a single-shaft hydraulic press with a molding pressure of 20-30 MPa. The green body is cylindrical with a diameter of 11-12 mm and a thickness of 5-6 mm. Step 5: Sinter the green billet in a muffle furnace under atmospheric conditions. The heating rate is 5℃ / min, the sintering temperature is 1080~1160℃, and the sintering time is 4~8 hours to obtain Ca3Ni2SiV2O. 12 Microwave dielectric ceramic.
[0026] Using the above preparation method, Ca3Ni2SiV2O was prepared at different sintering temperatures (1080℃, 1100℃, 1120℃, 1140℃, and 1160℃). 12 Microwave dielectric ceramics were used, and their microstructure and microwave dielectric properties were tested: X-ray powder diffraction was used to analyze the phase purity and crystal structure of the ceramics, scanning electron microscopy was used to observe the microstructure and elemental distribution of the ceramics, and the dielectric constant ε was measured using a vector network analyzer according to the Hakki-Coleman method. r Q×f value and temperature coefficient of resonant frequency τ f Value. Testing revealed that when the sintering temperature of the ceramic material is between 1080 and 1160℃, a single-phase Ca3Ni2SiV2O is formed. 12 The crystal structure is dense, stable, and exhibits excellent performance, making it a promising candidate formulation for high-performance microwave dielectric ceramic materials; the dielectric constant ε of the ceramic material... r Between 5.4 and 8.2, the quality factor Q×f is between 13710 GHz and 21960 GHz, and the temperature coefficient of resonant frequency τ f Between -50.2 ppm / ℃ and -42.6 ppm / ℃, the ceramic achieves excellent dielectric properties by simultaneously possessing a low dielectric constant and low sintering temperature while maintaining a high quality factor and a near-zero temperature coefficient of resonant frequency. The above-mentioned different sintering temperatures of Ca3Ni2SiV2O 12 For detailed XRD patterns of the microwave dielectric ceramic, please refer to the appendix. Figure 6 The measured microwave dielectric properties are detailed in Table 1.
[0027] Table 1. Ca3Ni2SiV2O at different sintering temperatures 12 Microwave dielectric properties of ceramics
[0028] Example 1 Using the above preparation method, the pre-calcination time of the dried powder is 4 hours, and the formed green body is sintered in an atmospheric atmosphere at 1080℃ for 4 hours.
[0029] The Ca3Ni2SiV2O prepared in this embodiment 12 See attached image for a microscopic photograph of the ceramic. Figure 1 As can be seen from the image, the ceramic's microstructure is dense and lacks obvious pores, indicating good crystallization. (Attached) Figure 6 The Ca3Ni2SiV2O 12 The XRD pattern of the ceramic shows that all X-ray diffraction peaks of the ceramic material sintered at 1080℃ can be characterized, and no second phase appears, indicating that Ca3Ni2SiV2O can be formed at this temperature. 12 Single phase.
[0030] Example 2 Using the above preparation method, the pre-calcination time of the dried powder is 6 hours, and the formed green body is sintered in an atmospheric atmosphere at 1140℃ for 6 hours.
[0031] The Ca3Ni2SiV2O prepared in this embodiment 12 See attached image for a microscopic photograph of the ceramic. Figure 2 As can be seen from the image, the ceramic's microstructure is dense and lacks obvious pores, indicating good crystallization. (Attached) Figure 6 The Ca3Ni2SiV2O 12 The XRD pattern of the ceramic shows that all X-ray diffraction peaks of the ceramic material sintered at 1140℃ can be characterized, and no second phase appears, indicating that Ca3Ni2SiV2O can be formed at this temperature. 12 Single phase.
[0032] Example 3 Using the above preparation method, the pre-calcination time of the dried powder is 8 hours, and the formed green body is sintered in an atmospheric atmosphere at 1160℃ for 8 hours.
[0033] The Ca3Ni2SiV2O prepared in this embodiment 12 See attached image for a microscopic photograph of the ceramic. Figure 3 As can be seen from the image, the ceramic's microstructure is dense and lacks obvious pores, indicating good crystallization. (Attached) Figure 6 The Ca3Ni2SiV2O 12 The XRD pattern of the ceramic shows that all X-ray diffraction peaks of the ceramic material sintered at 1160℃ can be characterized, and no second phase appears, indicating that Ca3Ni2SiV2O can be formed at this temperature. 12 Single phase.
[0034] Comparative Example 1 Using the above preparation method, the pre-calcination time of the dried powder is 5 hours, and the formed green body is sintered in an atmospheric atmosphere at 1060℃ for 8 hours.
[0035] The Ca3Ni2SiV2O prepared in this comparative example 12 See attached image for a microscopic photograph of the ceramic. Figure 4 As can be seen from the figure, the crystal structure of the ceramic exhibits obvious pores, indicating that the ceramic cannot be sintered to be dense and therefore cannot obtain good dielectric properties.
[0036] Comparative Example 2 Using the above preparation method, the pre-calcination time of the dried powder is 4 hours, and the formed green body is sintered in an atmospheric atmosphere at 1200℃ for 6 hours.
[0037] The Ca3Ni2SiV2O prepared in this comparative example 12 See attached photos of the actual ceramic pieces. Figure 5 As can be seen from the figure, the sintered ceramic body has changed color and become uneven due to local melting, and the ceramic cannot obtain good dielectric properties.
[0038] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
[0039] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range. The terms "comprising," "including," "having," "containing," etc., as used herein are open-ended terms, meaning they include but are not limited to.
[0040] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
Claims
1. A low dielectric constant garnet-type microwave dielectric ceramic, characterized in that, The chemical formula is Ca3Ni2SiV2O 12 .
2. The method for preparing low dielectric constant garnet-type microwave dielectric ceramics according to claim 1, characterized in that, Includes the following steps: S1, the original powders of CaCO3, NiO, V2O5 and SiO2 are arranged according to Ca3Ni2SiV2O 12 The components are weighed and mixed. S2, Wet ball mill the original powders weighed in step S1 to obtain a mixed slurry; S3, the mixed slurry is dried and pre-calcined to obtain mixture A; S4, add binder to mixture A and granulate, then shape to obtain green body; S5, the green blank is sintered to obtain Ca3Ni2SiV2O 12 Microwave dielectric ceramics.
3. The method for preparing low dielectric constant garnet-type microwave dielectric ceramics according to claim 2, characterized in that, The purity of the original powders of CaCO3, NiO, V2O5 and SiO2 in step S1 is not less than 99.99%.
4. The method for preparing low dielectric constant garnet-type microwave dielectric ceramics according to claim 2, characterized in that, In step S2, the wet ball milling time is 6 hours, and the ball milling medium is deionized water.
5. The method for preparing low dielectric constant garnet-type microwave dielectric ceramics according to claim 2, characterized in that, The pre-firing in step S3 is carried out in an atmospheric atmosphere, with a heating rate of 5℃ / min, a pre-firing temperature of 900℃, and a pre-firing time of 4~8 hours.
6. The method for preparing low dielectric constant garnet-type microwave dielectric ceramic according to claim 2, characterized in that, In step S4, the mass of the binder accounts for 1.5 to 3% of the mass of mixture A.
7. The method for preparing low dielectric constant garnet-type microwave dielectric ceramics according to claim 6, characterized in that, In step S4, the adhesive is a 5% polyvinyl alcohol solution.
8. The method for preparing low dielectric constant garnet-type microwave dielectric ceramics according to claim 2, characterized in that, The sintering in step S5 is carried out in an atmospheric atmosphere, with a heating rate of 5℃ / min, a sintering temperature of 1080~1160℃, and a sintering time of 4~8 hours.
Citation Information
Patent Citations
Low-dielectric high-entropy microwave dielectric ceramic with garnet structure and preparation method of low-dielectric high-entropy microwave dielectric ceramic
CN118791286A